Pertanggungjawaban Hukum atas Keterlambatan Pemberitahuan Akuisisi Asing kepada Komisi Pengawas Persaingan Usaha - Muchamad Arifin (Universitas Islam Indonesia, 2017)
This study examines the authority of KPPU (Indonesian Business Competition Supervisory Commission) in the case of late notification of the acquisition of Woongjin shares by Toray Materials. The acquisition is carried out by a foreign company that is not domiciled in Indonesia, so the act is outside the jurisdiction of the Republic of Indonesia. This study also examines the legal liability of Toray Materials for the late notice of Woongjin share acquisition. Toray Materials reasoned that the delay is due to their having insufficient information about the laws and regulations in Indonesia. This study is normative legal research using a legislative approach and a case-study approach. Based on the results, we find that KPPU has the authority over the corporate action by Toray Materials in performing their acquisition of Woongjin shares. Based on the principle of legal duty by mistake element, Toray Materials has the legal responsibility for their action. Their mistake is a form of negligence.Keywords: Business competition; share acquisition